Podejście multiagencyjne w procesie readaptacji osób opuszczających zakłady karne - Barczykowska, Agnieszka; Muskała, Maciej (Wydawnictwo Naukowe UAM, 2015)
One of the biggest problems of modern pedagogy is the process of social re- adaptation of exprisoners. Despite extensive knowledge of the course of the process, rehabilitation results continue to be unsatisfactory. One of the attempts to break the deadlock is the US model of the Transition from Prison to the Community. It represents the best thinking and evidence about how to manage transition and successful reentry with a view to community safety and reduced victimization.
Multi-agency Work in the Process of Social Readaptation of Persons Released from Prisons
Keywords: convicted; readaptation; collaboration; prison; institutions